1985
DOI: 10.1021/jf00062a028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on flatus-producing factors in legumes

Abstract: The effect of various treatments, viz., (1) soaking in plain water and sodium bicarbonate solution, (2) cooking of soaked seeds, (3) autoclaving of soaked seeds, (4) germination, and (5) frying of germinated seeds, was studied by measuring the oligosaccharide contents of five commonly grown legumes, viz., Rajmah (Phaseolus vulgaris), Bengal gram (Cicer arietinium), black gram (Phaseolus mungo), red gram (Cajanus cajan), and broad bean (Vicia faba). The contents of sucrose, raffinose, stachyose, and verbascose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
29
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 2 publications
13
29
0
Order By: Relevance
“…Cooking of raw seeds and soaking of seeds in water, tamarind pulp extract, sodium bicarbonate solution and citric acid solution are responsible for a signi®cant reduction (P < 0.05) in the glucose and sucrose content, which was further reduced when the seeds were autoclaved. The present ®ndings are similar to those reported by Jood et al 41 in ®ve common legumes, who also observed signi®cant losses in the content of sucrose when the soaked seeds were cooked and autoclaved. Only a small amount of fructose was detected in cooked and autoclaved samples of raw seeds and seeds that were soaked in water and tamarind pulp extract.…”
Section: Cooking Autoclaving and Dry Heatingsupporting
confidence: 91%
See 2 more Smart Citations
“…Cooking of raw seeds and soaking of seeds in water, tamarind pulp extract, sodium bicarbonate solution and citric acid solution are responsible for a signi®cant reduction (P < 0.05) in the glucose and sucrose content, which was further reduced when the seeds were autoclaved. The present ®ndings are similar to those reported by Jood et al 41 in ®ve common legumes, who also observed signi®cant losses in the content of sucrose when the soaked seeds were cooked and autoclaved. Only a small amount of fructose was detected in cooked and autoclaved samples of raw seeds and seeds that were soaked in water and tamarind pulp extract.…”
Section: Cooking Autoclaving and Dry Heatingsupporting
confidence: 91%
“…These were further reduced signi®cantly (P < 0.05) by autoclaving. Similarly, other workers 41 have reported higher losses of raf®nose (63±89%), stachyose (75±89%) and verbascose (80±95%) in certain common legume seeds that were soaked in water and sodium bicarbonate solution for 12 h and then autoclaved. The same authors have also observed that soaking followed by autoclaving is more ef®cient for the reduction of a-galactosides than soaking followed by cooking.…”
Section: Cooking Autoclaving and Dry Heatingsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, to convert pigeonpea as a more acceptable source of inexpensive protein, it could be desirable to reduce the flatulence production. Possible approaches are: breeding of varieties low in these oligosaccharides, use of enzymes to reduce the oligosaccharide concentration (Reynolds, 1974) and soaking to germinate the seeds before cooking (Iyer et al,1980;Jood et al, 1985). Out of the three approaches the first and the last ones seems to be most pragmatic, as the enzymatic treatment tends to be either costly or it also alters the cooking quality of the grains which will not be preferred by the consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, seed quality improvement has become a major focus of research to reduce some of the anti-nutritional constituents such as raffinose family oligosaccharides (RFO) and tannins. Although RFO cause stomach discomfort, 2 tannins bind mineral ions thereby reducing their bio-availability to humans. 3 High-throughput transcriptomic studies involving deep sequencing have contributed valuable genomic resources for lentil.…”
Section: Introductionmentioning
confidence: 99%